The influence of cultivation technology elements on winter wheat productivity under conditions of western Polissya of Ukraine - Білітюк, А. П.; Гарбар, Л. А.; Циганчук, С. М. (Scientific Progress & Innovations, 2012)
The influence of sowing terms and seeding rates on formation of winter wheat varieties productivity under conditions of western Polissya of Ukraine has been studied. The obtained results shows that the highest yield of winter wheat varieties on sod-podzolic soils on background of N60Р60К60 was formed with sowing of Zolotokolosa variety at 30.09 and seeding rate 5 million vital seeds per hectare – 6.48 t/ha and Smuglyanka variety with sowing at 10.10 and the same seeding rate – 6.32 t/ha. The best grain quality was obtained with sowing of Smuglyanka variety at 20.10 and Zolotokolosa variety – 10.10.